Studying vibrio spp. in industrially polluted surface waters : difficulties and uncertainities during characterization - Alam, Sadia (BRAC University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Biotechnology, 2018.